Cost analysis of a patient navigation system to increase screening colonoscopy adherence among urban minorities. Issue 3 (25th July 2012) - Jandorf, Lina; Stossel, Lauren M.; Cooperman, Julia L.; Graff Zivin, Joshua; Ladabaum, Uri; Hall, Diana; Thélémaque, Linda D.; Redd, William; Itzkowitz, Steven H.
Abstract BACKGROUND: Patient navigation (PN) is being used increasingly to help patients complete screening colonoscopy (SC) to prevent colorectal cancer. At their large, urban academic medical center with an open‐access endoscopy system, the authors previously demonstrated that PN programs produced a colonoscopy completion rate of 78.5% in a cohort of 503 patients (predominantly African Americans and Latinos with public health insurance). Very little is known about the direct costs of implementing PN programs. The objective of the current study was to perform a detailed cost analysis of PN programs at the authors' institution from an institutional perspective. METHODS: In 2 randomized controlled trials, average‐risk patients who were referred for SC by primary care providers were recruited for PN between May 2008 and May 2010. Patients were randomized to 1 of 4 PN groups. The cost of PN and net income to the institution were determined in a cost analysis. RESULTS: Among 395 patients who completed colonoscopy, 53.4% underwent SC alone, 30.1% underwent colonoscopy with biopsy, and 16.5% underwent snare polypectomy. Accounting for the average contribution margins of each procedure type, the total revenue was $95, 266.00. The total cost of PN was $14, 027.30. Net income was $81, 238.70. In a model sample of 1000 patients, net incomes for the institutional completion rate (approximately 80%), the historic PN program (approximately 65%), and the national average (approximately 50%) were compared. The current PN program generated additional net incomes of $35, 035.50 and $44, 956.00, respectively. CONCLUSIONS: PN among minority patients with mostly public health insurance generated additional income to the institution, mainly because of increased colonoscopy completion rates. Cancer 2013. © 2012 American Cancer Society.